2014
DOI: 10.2135/cropsci2013.05.0355
|View full text |Cite
|
Sign up to set email alerts
|

A Prioritized Inventory of Crop Wild Relatives and Wild Harvested Plants of Italy

Abstract: The aim of this study was to construct a solid basis for developing a crop wild relatives (CWR) and wild harvested plants (WHP) conservation strategy at the European and national levels. To this end we (i) worked out an annotated and synonymized Working Database of the Italian Vascular Plants, (ii) worked out a full CWR–WHP checklist for Italy, (iii) worked out a prioritized CWR and WHP inventory, (iv) identified native taxa with an ascertained utility for breeding, and (v) on the basis of a gap analysis case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…A specific agro-biodiversity conservation plan is needed for Europe because the region includes the Mediterranean basin biodiversity hotspot and is rich in both crop wild relatives and landraces that are still cultivated [ 22 , 27 – 36 ], while high population density, widespread industrial and agricultural activities and the effects of climate change make biodiversity vulnerable. In fact, as can be seen from data of the European Union which covers a large part of Europe, and in spite of the European Union network of protected areas, the existence of quite detailed information systems on nature conservation, and of common agro-environmental policies, biodiversity decline has not been halted in recent years (European Parliament Resolution 2016) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A specific agro-biodiversity conservation plan is needed for Europe because the region includes the Mediterranean basin biodiversity hotspot and is rich in both crop wild relatives and landraces that are still cultivated [ 22 , 27 – 36 ], while high population density, widespread industrial and agricultural activities and the effects of climate change make biodiversity vulnerable. In fact, as can be seen from data of the European Union which covers a large part of Europe, and in spite of the European Union network of protected areas, the existence of quite detailed information systems on nature conservation, and of common agro-environmental policies, biodiversity decline has not been halted in recent years (European Parliament Resolution 2016) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inventories must be made as the first step to conserve CWRs for candidate species. CWR inventories can be (and have been) made at international, national, and regional levels (Berlingeri & Crespo, ; Khoury et al., ; Landucci et al., ; Maxted & Kell, ) or can be focused on a particular crop taxon (Castaneda‐Alvarez et al., ; Khoury et al., ; Zhao et al., ). Currently, several of these inventories have deposited information such as taxonomic origins, regional priority categories, and proposed conservation strategies into electronic databases (Table ).…”
Section: Conservation Of Cwr and Accessibility To Breeders And Genetimentioning
confidence: 99%
“…Prioritizing CWRs is important for efficient conservation efforts. For various reasons, some national or local inventories are focused only on major crops (Berlingeri & Crespo, ; Khoury et al., ; Landucci et al., ; Maxted & Kell, ; Vincent et al., ). In these inventories, higher priorities are given to the wild relatives falling into primary or secondary GPs over other more distant ones, as it is relatively easy to transfer traits between species within the primary GP.…”
Section: Conservation Of Cwr and Accessibility To Breeders And Genetimentioning
confidence: 99%
“…7. Ancona: The presence of a population in Ancona was mentioned byLanducci et al (2014), who reported it as a new finding made in 2012. However, several…”
mentioning
confidence: 92%